MUTU LAYANAN PENDIDIKAN MADRASAH TSANAWIYAH HIDAYATUL MUBTADIIN JATI AGUNG LAMPUNG SELATAN - Sarpendi Sarpendi (FKIP, Universitas Palangka Raya, 2022)
The purpose of this study was to determine the quality of educational services in the aspects of physical evidence, aspects of empathy, aspects of reliability in Madrasah Tsanawiyah Hidayatul Mubtadiin. This study used a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. This participatory observation technique was carried out to observe the geographical location in the form of a location plan and environmental conditions, vision, mission, strategy and motto of the Nurul Hikmah Tsanawiyah Madrasah School. Interviews were conducted to determine the quality of educational services in the physical evidence aspect, the empathy aspect, and the reliability aspect. Based on the results of the description that has been described that the quality of service aspects of physical evidence (tangible) at MTs Hidayatul Mubtadiin has adequate physical conditions, the availability of facilities and infrastructure that support learning, service aspects of empathy (emphaty) has good service quality. This can be interpreted that the ability of school principals, teachers and staff to communicate with students and parents, such as paying attention to students who have learning abilities have not yet reached the KKM by providing additional learning after school hours are over, service aspects of reliability (reliability) have service quality already in line with customer expectations such as competent teachers and supportive teacher educational backgrounds.